Cloud Computing and Document Management in a BPO Services Company Located in Magdalena del Mar District (Lima-Peru), 2021 - Cerna Romero, Yusuke Abraham (2022)
As the 21st century continues to bring about technological changes, organizations have undergone radical transformations and have had to implement technological tools to continue to compete in the market. In the wake of these changes, cloud computing emerged as an instrument to optimize business management. The main purpose of this research was to determine the relationship between cloud computing and document management in a BPO services company. The research’s variables were subdivided into three dimensions for a better understanding. The research followed a quantitative approach, correlational scope and used a non-experimental cross-sectional correlational-causal design. The sample was comprised of 45 employees of the company working in the departments of Human Resources, Innovation Management and IT Management, who were provided with an 18-item Likert scale questionnaire. Following the processing and analysis of the information, a direct and significant correlation was determined between cloud computing and document management (p < .05), as a Spearman correlation coefficient of .596 was obtained.